Co-management of large-scale and medium-scale fisheries: An assessment of the fishery tax system in Indonesia. (February 2023) - Halimatussadiah, Alin; Yamazaki, Satoshi; Nichols, Rachel; Muawanah, Umi; Afifi, Fachry Abdul Razak; Adriansyah, Muhammad
Abstract: Many fish stocks are jointly exploited by industrial vessels that employ modern fishing technologies and small- to medium-scale vessels that rely on simple gears. For the effective management of these shared stocks, it is imperative to understand how different policy options influence the behavior of fishing vessels of different sizes. A fishery tax could be a viable option where other popular market-based instruments, such as individual transferable quotas, cannot be adopted. In this study, we developed a model that incorporates the interaction between large- and medium-scale fishing vessels to evaluate the impact of alternative tax schemes. The model is parameterized using the skipjack ( Katsuwonus pelamis ) purse-seine fishery in Indonesia, which has over 20 years of experience in fishery taxes. The results show that the current tax system has a limited impact on reducing fishing pressure, as tax payments are determined by the pre-production characteristics of fishing entities. Moreover, vessels below 30 GT are exempt from taxes, giving incentive for fishers to invest in vessels below or far above 30 GT. When taxes are imposed on only one vessel group, the harvest reduction by this vessel group could be offset by an increase in the harvest by untaxed vessels. Imposing a production-based tax on both large and medium vessels results in a more balanced outcome in terms of the distribution of fishery benefits and vessel capacity across regions. We discuss the social and institutional implications of implementing a production-based taxation system to promote efficient and equitable resource use in Indonesian fisheries.